Roman Lamps from the National Museum of History of Ukraine - Sheiko, I.M.; Puklina, O.O. (Археологія, 2019)
The article deals with a collection of ancient lamps from the funds of the National Museum of History of Ukraine, covering the period of the first centuries AD. Centers of production and dating are clarified.